5ive Charm Center / Norazian Subari ... [et.al] - Subari, Norazian; Abdul Wahab, Noraziah; Mat, Normaliza (Faculty of Electrical Engineering, 2004)
After considering few aspects, we finally decide to propose a book store cum cyber cafe for our business plan. We propose the name of our business is "5IVE CHARM CENTRE". Our business is based on partnership and is categories as a trading business. Our business is about selling books. We offer a wide variety reading material such as references books (primary and secondary school), novels, story books, newspapers and magazines. Beside that, we are also planning to provide internet services in our business. Our customer can surf internet to find out information, to get news information, chatting and sending email. In other hand, we also provide printing and scanning services for our customers. Our business will be located at Plaza Alam Sentral. We find this location is strategic because there are many residential areas around it. Furthermore, many high institutions located near the Plaza Alam Sentral such as UiTM, INPENS, UNISEL and POLYTECHNINC Shah Alam. That mean our target will be larger because our focus is students.